2015
DOI: 10.1111/trf.13000
|View full text |Cite
|
Sign up to set email alerts
|

In vitro variables of buffy coat–derived platelet concentrates with residual plasma of down to 10% are stably maintained in new‐generation platelet additive solutions

Abstract: Preparation of BC-derived PCs with minimal plasma concentrations as low as 10% is feasible. Late-generation PASs satisfactorily preserve the in vitro quality of such PCs during storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Glucose is essential to maintain in vitro PLT quality, whereas other fuels such as acetate and fatty acids act as energy sources. Gravemann et al reported that metabolic, aggregation and activation markers still indicated that PLT quality was well preserved despite very low glucose concentrations in SSP+ PCs (Gravemann et al, 2015). Similarly, in this study, although glucose concentrations in the test units decreased below 2·0 mmol/L by Day 7, HSR and CD62P expression were comparable or superior to those in the control units.…”
supporting
confidence: 63%
“…Glucose is essential to maintain in vitro PLT quality, whereas other fuels such as acetate and fatty acids act as energy sources. Gravemann et al reported that metabolic, aggregation and activation markers still indicated that PLT quality was well preserved despite very low glucose concentrations in SSP+ PCs (Gravemann et al, 2015). Similarly, in this study, although glucose concentrations in the test units decreased below 2·0 mmol/L by Day 7, HSR and CD62P expression were comparable or superior to those in the control units.…”
supporting
confidence: 63%
“…However, there is growing evidence that a plasma carryover below 30% may provide sufficient glucose to support in vitro PLT quality during storage in SSP1. 3,13,15,16 The aim of this study was to determine whether reducing the plasma carryover from 30% to 20% supports PLT metabolism and quality over an extended storage period of 10 days. Biochemical changes, as well as markers of PLT activation and apoptosis, were assessed to understand the effect of storing PLTs in reduced plasma for extended periods.…”
Section: Results: Glucose Exhaustion Occurred In the 20%mentioning
confidence: 99%
“…New-generation PASs have been formulated to contain glucose and/or bicarbonate, and results demonstrate that PLT quality can be supported with plasma carryover as low as 5%. 16,39,40 However, none of these studies examined phosphatidylserine exposure or other markers of PLT quality beyond 7 days. As such, further work should be carried out to examine the ability of these glucose-containing ASs to prevent apoptosis following extended storage.…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, apheresis can be an alternative to manual procedures, inducing oxidative stress and platelet activation in a lesser extent, delaying the appearance of storage lesion, improving the conservation during the 5 days that they are preserved [17][18][19]. However, the level of oxidative stress in relation to the storage lesion comparing the two methods of production of platelet concentrates still remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%